Careers in journalism for the new woman - Rosenfeld, Megan. 4 0 16; 5 (New York : Watts, 1977)
Discusses journalism as a career with attention to preparation needed, schools, types of jobs on various publications, and women in American journalism.
Includes index.
Bibliography: p. [109]-110.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Vocational guidance;Vocational guidance. -- Journalism;Women in journalism;Journalism;Women in journalism.;Vocational guidance. -- 20 -- Juvenile literature.;Juvenile literature; 20; 2